PEMAHAMAN KONSEP MAHASISWA DALAM MENYELESAIKAN MASALAH FUNGSI PEMBANGKIT DITINJAU DARI SELF- EFFICACY - SITI NURIYATIN; Dewi Sukriyah (JEDMA Jurnal Edukasi Matematika, 2023)
Self-efficacy has a role in one's success in achieving goals. Self-efficacy is a factor that can encourage students to understand concepts correctly. This study describes students' understanding of concepts in solving generating function problems based on self-efficacy. The subjects were 23 students who were given self-efficacy questionnaires and tests related to generating functions. The results of students' understanding of concepts with very high self-efficacy are very good. Students who have high self-efficacy have different levels of understanding of concepts. Sequentially, their level of understanding of the concept is very high, sufficient, and high. Understanding the concept of students with sufficient self-efficacy is less, sufficient, very high. Students with a specific level of self-efficacy have different levels of conceptual understanding in some of the sub-materials being studied. Students who have the same level of self-efficacy have the opportunity to have different levels of understanding of concepts.